High-power operation of coherently coupled tapered laser diodes in an external cavity - Schimmel, G.; Doyen, I.; Janicot, S.; Hanna, M.; Georges, P.; Lucas-Leclin, G.; Decker, J.; Crump, P.; Erbert, G.; Kaunga-Nyirenda, S.; Moss, D.; Bull, S.; et al. (2016)
We demonstrate a rear-side phase-locking architecture with two high-brightness diode lasers. This technique is based on the passive phase-locking of emitters in an external cavity on their rear facet, and their coherent combination on the front facet. Two high-brightness high-power tapered laser diodes are coherently combined using a Michelson-based cavity. The combining efficiency is above 80% and results in an output power of 6.7 W in a nearly diffraction-limited beam. The rear-side architecture is then used with a laser bar of 5 tapered emitters using an interferometric extended cavity, based on a diffractive optical element. We describe the experimental evaluation of the diffractive optical element, and the phase-locked operation of the laser bar.